1997
DOI: 10.1042/cs0930335
|View full text |Cite
|
Sign up to set email alerts
|

Mutations at the Lipoprotein Lipase Gene Locus in Subjects with Diabetes Mellitus, Obesity and Lipaemia

Abstract: 1. The common association of obesity, diabetes mellitus and hyperlipidaemia may have a primary aetiological basis. Insulin resistance has been postulated as a possible cause, but defects in the plasma transport of triacylglycerol or fatty acids could also be primary determinants. 2. We have therefore studied 18 patients with diabetes mellitus, obesity and severe hypertriglyceridaemia for defects of a key protein involved in the clearance of plasma triacylglycerols, lipoprotein lipase. 3. DNA was prepared from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 23 publications
2
7
0
Order By: Relevance
“…We did not, however, detect LPL gene alterations in patients with mild hypertriglyceridaemia, in agreement with a previous study of diabetic and hypertriglyceridaemic members of Type II diabetic families [42]. In Type II diabetes with severe hypertriglyceridaemia, LPL gene mutations were reported either in isolated cases [9] or in a small group of patients [43]. Lipoprotein lipase activity in plasma after heparin treatment and in adipose tissue is decreased in hypertriglyceridaemic Type II diabetic patients and in insulin-resistant obese subjects [30,44].…”
Section: Discussionsupporting
confidence: 76%
“…We did not, however, detect LPL gene alterations in patients with mild hypertriglyceridaemia, in agreement with a previous study of diabetic and hypertriglyceridaemic members of Type II diabetic families [42]. In Type II diabetes with severe hypertriglyceridaemia, LPL gene mutations were reported either in isolated cases [9] or in a small group of patients [43]. Lipoprotein lipase activity in plasma after heparin treatment and in adipose tissue is decreased in hypertriglyceridaemic Type II diabetic patients and in insulin-resistant obese subjects [30,44].…”
Section: Discussionsupporting
confidence: 76%
“…Individual variability in the postprandial lipemic response is usually greater than that observed in the fasting state and it appears to be modulated by environmental and genetic factors (Mero et al 1998). This concept is supported by studies showing that certain polymorphisms at candidate gene loci (the APOA1-APOC3-APOA4 gene complex, APOB, APOE,LIPC,CETP,FABP2 and LPL) are associated with variability in postprandial clearance of lipoprotein (Knudsen et al 1997, Zhang et al 1997, Agren et al 1998, Ostos et al 1998, Fisher et al 1999, Hockey et al 2001, Ordovas 2001.…”
Section: Introductionmentioning
confidence: 56%
“…Indeed, the possibility that a single nucleotide polymorphism in the promoter region, which impairs the binding of transcription factor Oct-1 and reduces transcription activity to 15% or less, is related to FCHL and ischemic heart disease has been suggested 43) . Reports from Western countries include a study in which LPL gene abnormalities were observed in 10% of patients with type hyperlipoproteinemia 44) , but Arai et al found no LPL gene mutations in any of 100 Japanese subjects with a serum TG level of 400-1,000 mg/dl examined 45) . Generally, poor control of blood glucose in diabetic patients is the most frequent acquired stressor, but drinking, estrogen, steroids, pregnancy, Zoloft (selective serotonin reuptake inhibitor type antidepressant), isotretinoin (treatment for acne), diuretics, -blockers, HIV protease inhibitors, dysproteinemia, multiple myeloma, SLE, malignant lymphoma, etc., have also been reported.…”
Section: Fig 2 Etiological Factors Underlying Primary Type V Hyperlmentioning
confidence: 99%